Penelitian penerapan SLiMS dalam pengolahan perpustakaan pada database Google Scholar: sebuah narrative literature review - Fani, Zulfati Amelia; Rukmana, Evi Nursanti (Jurnal Informatio, 2022)
Electronic catalogs have brought about a change in cataloging patterns in libraries. The existence of a catalog based on SLiMS is a choice of electronic catalogs that are easy to uses in libraries. This study aims to determine the research on the application of SLiMS in library processing on the Google Scholar database which analyzes the themes/topics, research methods, and research results used. The research method uses an qualitative approach through a narrative literature review on eight references indexed by the Google Scholar database with a range of publications from 2017 to 2022. The results shows that research on the application of SLiMS in a library processing on the Google Scholar database is a research that is mostly carried out in various libraries. According to the research theme/topic, the SLiMS studied were from the field of university libraries and public/city libraries. As for the research analysis method, SLiMS has been widely studied using qualitative and quantitative methods. The eight references analyzed have research results showing that SLiMS provides convenience and benefits in the continuity of collection processing activities in the library. The SLiMS electronic catalog has helped librarians in collection processing and librarian development.